Exploring the interplay of semantic knowledge in bilingual children: heritage language and second language - Kan, Pui Fong; Yim, Dongsun; Brennan, Christine (Frontiers in Language Sciences, 2024)
This study investigates the semantic development of heritage bilingual preschool children aged 3 to 5 who acquire Cantonese as their heritage language (HL) at home and English as their community language (L2) in school settings. The research examines how bilingual children organize and access their vocabulary in two distinct languages and how their heritage language influences semantic development in L2. We examined their performance in Word Association Identification Task (WAID) and Word Association Task (WAT) in both languages. Results showed that they perform similarly in WAID in both languages, with higher accuracy in semantically unrelated conditions. The WAT results showed that children had more syntagmatic responses in Cantonese than in English, but had similar paradigmatic responses in both languages. Regression analysis revealed that paradigmatic responses in Cantonese predicted children's English paradigmatic responses. Their English paradigmatic responses were also associated with WAID performance in English. This study contributes to understanding heritage bilingual children's semantic development, with implications for education and language support.